Optimalisasi Pemanfaatan Limbah Minyak Jelantah melalui Pelatihan Pembuatan Sabun Cair Ramah Lingkungan di Kelurahan Rawajati - Hastuti, Wedia; Irma Maria Dulame (Jurnal Abdi Masyarakat Nusantara, 2025)
The majority of used cooking oil waste produced by household activities in Rawajati Subdistrict is commonly discarded directly into water channels or soil, which may lead to environmental pollution and a decline in public health standards (Widodo & Hidayat, 2021). The community’s limited knowledge of waste cooking oil management is one of the main causes of this problem. This community service activity aimed to provide training on processing used cooking oil into environmentally friendly liquid soap products with both practical and economic value. The implementation approach was carried out in three phases: preparation (including observation and coordination with the subdistrict office), execution covering awareness activities on the impacts of used cooking oil management training, practical demonstrations of liquid soap production, hands-on implementation, and subsequent evaluation through skill competency and satisfaction assessments. The event was participated in by 30 individuals, consisting of housewives and members of the Family Welfare Movement (PKK). The results of the training showed that 90% of participants were able to perform the liquid soap production process on their own, and 80% expressed interest in developing the product into a possible home-based enterprise. This initiative effectively enhanced the community’s understanding and abilities in handling used cooking oil waste, providing a practical approach to mitigating environmental pollution. This program carries the potential to foster the growth of creative economic initiatives centered on household waste management in the Rawajati Subdistrict.